The Monstrosity of Christ : Paradox or Dialectic? - Žižek, Slavoj (Book collections on Project MUSE., 2009)
A militant Marxist atheist and a "Radical Orthodox" Christian theologian square off on everything from the meaning of theology and Christ to the war machine of corporate mafia.